Diffusiophoresis of charged particles and diffusioosmosis of electrolyte solutions. (August 2016) - Keh, Huan J.
Abstract: A review is presented on the theoretical basics and recent developments about the diffusiophoresis of charged particles and diffusioosmosis of electrolyte solutions driven by imposed electrolyte concentration gradients with particular emphasis on the principal analytical formulas and their physical interpretations. For diffusiophoresis, migrations of particles with thin polarized electric double layers but arbitrary zeta potentials and with arbitrary double layers but relatively low surface potentials are both discussed in detail, covering not only diffusiophoresis of single particles but also their motions near solid boundaries or other particles. For diffusioosmosis, fluid flows along single plane walls, in micro/nano-channels, and in porous media are considered, in which the solid walls may have arbitrary zeta potentials or surface charge densities, and both the effect of the lateral distribution of the diffuse ions and the relaxation effect in the double layers on the tangential electric field induced by the prescribed electrolyte concentration gradient are included. Graphical abstract: Highlights: Theoretical basics about diffusiophoresis and diffusioosmosis are reviewed. Principal analytical formulas of diffusiophoresis and diffusioosmosis are presented. Surfaces with arbitrary double layer, charge density, and potential are considered. Boundary and particle-interaction effects on diffusiophoresis are presented. Diffusioosmotic velocities in various channels and porous media are presented.